Exploring the Anxiety Level and Emerging Issues of WFH Mothers Amidst the Pandemic - Santos, Geraldine; Arguelles-Manda, Aimee Rose; De Guzman, Ma. Jeanette; Equiza, Cynthia (Social Sciences and Development Review, 2023)
The COVID-19 pandemic continues to evolve, as does the understanding of the SARS-CoV-2 virus and the response needed to control the spread and impact of the virus (WHO, 2022). The global public health risk was very high in WHO’s most recent global rapid risk assessment, conducted on 07 January 2022. The spread of COVID-19 has thrown work and life into terribly uncertain waters. The lockdowns and work-from-home setups brought the already precarious position–family balance into direct conflict for many working parents, with even more significant impact on mothers. A mixed-method convergent parallel design was utilized to examine the anxiety level using the Burns Anxiety Inventory (BAI) and a questionnaire to explore the issues of work-from-home mothers amidst the pandemic. Quantitative and qualitative data were collected simultaneously and weighed equally in the analysis phase. This study used the epistemological lens as its theoretical contribution to understand and help working mothers cope with stress and be used as a basis for implementing mental health programs amidst and beyond the COVID-19 pandemic. Participants for the quantitative and qualitative phase included work-from-home mothers (N = 276) affiliated in the academic sector in Metro Manila, Philippines. Results showed most of the respondents scored from (11-20), 57 or 20% have Mild Anxiety while (5-10) 51 or 18% have Borderline Anxiety, followed by respondents (31-50) 50 or 18% with Severe Anxiety, and 24 or 8% of the respondents scored (51-99) with Extreme Anxiety or Panic. This means that despite the challenges brought about by the pandemic, the majority of the work from home mother respondents still managed to cope and keep up with the work-life difficulties, with only 8% of the sample population suffering from Extreme Anxiety or Panic. The results of this study are expected to give insights for management as it provides care for the mental health of the mother employees through effective and sustainable mental health programs amidst and beyond the pandemic. Emerging issues were time management, explicitly setting boundaries between mother roles and work, non-conducive workspace, and technology-related issues. However, mothers appreciated the opportunity to spend more time with family the convenience and safety of working from home.